2013
DOI: 10.1021/ol400865b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfonic Acid Derivatives by Oxidative Deprotection of Thiols Using tert-Butyl Hypochlorite

Abstract: Starting from alkyl halides or Michael acceptors, thioacetates were prepared in situ and further treated with t-BuOCl, affording the corresponding sulfonyl chlorides which were trapped with nucleophiles such as water, alcohol, or amines. The three steps can be achieved in a one-pot procedure. Oxidative deprotection also proved to be efficient with S-trityl and S-tert-butyl groups, making it a convenient route toward cysteic acid derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…The fact that the both procedures are applicable for conversion of some thiols to sulfonic acids was further demonstrated by facile conversion of cysteine to its sulphonic acid derivative, namely, cysteic acid, Scheme ; the latter is the end product of oxidation of cysteine and cystine, and is generally measured as surrogate for total cysteine and cystine content in a given protein subsequent to oxidation. Accordingly, the reaction of N ‐acetyl protected methyl ester of L‐cysteine with Oxone yielded the corresponding sulfonic acid in 58 % isolated yield over 48 h, while the reaction with KBrO 3 led to the acid in 87 % yield, albeit over an extended period of 3d …”
Section: Resultsmentioning
confidence: 99%
“…The fact that the both procedures are applicable for conversion of some thiols to sulfonic acids was further demonstrated by facile conversion of cysteine to its sulphonic acid derivative, namely, cysteic acid, Scheme ; the latter is the end product of oxidation of cysteine and cystine, and is generally measured as surrogate for total cysteine and cystine content in a given protein subsequent to oxidation. Accordingly, the reaction of N ‐acetyl protected methyl ester of L‐cysteine with Oxone yielded the corresponding sulfonic acid in 58 % isolated yield over 48 h, while the reaction with KBrO 3 led to the acid in 87 % yield, albeit over an extended period of 3d …”
Section: Resultsmentioning
confidence: 99%
“…In addition to the environment-and worker-friendly advantages of this method, the neutral conditions make it applicable to substrates with acid-sensitive functional groups, as demonstrated by Bischoff's report. 5 As a convincing example, the Cbz-protected 2-aminoethanesulfonyl chloride and pyridine-2-sulfonyl chloride could be successfully synthesized in good yields under the current neutral conditions, and the acid-sensitive Cbz-protecting group was not affected.…”
Section: Scheme 3 Large-scale Synthesismentioning
confidence: 97%
“…4 Recently, Bischoff and co-workers reported that tert-butyl hypochlorite is suitable for converting thiols, disulfides, thioacetic esters, and sulfides with S-tert-butyl or S-trityl groups. 5 The employment of tert-butyl hypochlorite has many advantages, such as good solubility in organic solvents, easy availability from commercial sources or through straightforward organic synthesis, safe handling without rubber, easy-to-remove byproducts, and neutral conditions.…”
mentioning
confidence: 99%
“…46 It can be achieved by reaction of disulfides with NCS, 47 oxidation of the biologically relevant sulfides 48 with chlorine on an industrial scale, 49 and transformation of S-alkylisothiourea salts with NaClO 2 , 50 NaClO 51 and NCS. 52 In addition, sulfonyl chlorides can be prepared from other different sulfur functionalities, [53][54][55] by oxidation of triisopropylsilanylsulfanyls with KNO 3 /SO 2 Cl 2 , 56 oxidation/ chlorination of thioacetates, 57 reaction of the Grignard reagents with SO 2 58 and DABSO, 59 and transformation of the lithiated aromatics with SO 2 and NCS, 60 and others. Meerwein's batch approach 61 was successfully modified by chlorosulfonation with SO 2 /CuCl 2 of an in situ generated diazonium salt by using a continuous flow reactor.…”
Section: Introductionmentioning
confidence: 99%